INTERNATIONAL MEDICAL TOURISM: TRENDS IN DEVELOPMENT AND THE ROLE OF DENTAL SERVICES (INNOVATIVE ECONOMY, 2024)
Ivashchuk O.V., Stakhanskyi O.O. INTERNATIONAL MEDICAL TOURISM: TRENDS IN DEVELOPMENT AND THE ROLE OF DENTAL SERVICESPurpose. The aim of the article is to study current trends in the development of international medical tourism with an emphasis on its dental segment, and to identify factors that influence the attractiveness of countries in the field of dental tourism.Methodology of research. The methodological basis of the research is a comprehensive approach to the use of basic methods of scientific knowledge. General scientific and special methods were used in the process of research, in particular, analysis and synthesis – to systematize the main trends in the international tourism market; methods of induction and deduction – for forming logical conclusions about the state of development of the medical tourism and dental services market; comparative analysis - to assess the cost and quality of dental services in different countries. The method of content analysis was used to study the offers and marketing strategies of dental clinics for foreign patients, and the comparative analysis and case study method was used to study and compare successful practices of leading countries in the field of dental tourism.Findings. The active development of international tourism, despite geopolitical and economic challenges, is substantiated. The dynamics of international tourist arrivals, a significant part of which are private visits, are analysed. Health care is identified as one of the reasons for international tourism, which has led to the active development of medical tourism. The categories of medical tourism are detailed; the main official recommendations in this area and existing codes of medical ethics are analysed. The positions of countries according to the Medical Tourism Index are assessed. It is argued that dental treatment is one of the key segments in medical tourism. An analysis of the market of dental services was carried out and the main countries of their provision for foreign patients were identified, the key factors contributing to their popularity were clarified. The main risks in the field of dental tourism have been identified. The potential of Ukraine in terms of the development of dental tourism is substantiated and specific measures are proposed to increase its attractiveness among foreign tourists.Originality. A comprehensive analysis of the specifics of the development of dental services as a key segment of international medical tourism was conducted, in particular: the role of dental services in the structure of international medical tourism was identified; identified key factors in patients' choice of dental services abroad, including economic (cost), quality (level of medical standards), social and cultural aspects; conducted a comparative analysis of leading countries in the field of dental tourism, which allowed determining their competitive advantages; the risks in dental tourism are substantiated; the problems of developing dental tourism in Ukraine are identified and the main ways to increase its attractiveness are proposed.Practical value. The proposed recommendations and drawn conclusions can be used in developing a state strategy for the development of medical tourism with an emphasis on dental services as a promising sector and the popularization of dental tourism in Ukraine; representatives of the tourism business and medical institutions to intensify the development of dental tourism and develop comprehensive service packages combining dental services with cultural and recreational programs; by consumers of dental tourism services for an objective assessment of its benefits and risks.Key words: globalization, geopolitical and economic challenges, international tourism, medical tourism, dental services, dental tourism, competition, price factors, medical ethics, infrastructure, innovative technologies.
Keywords: globalization; geopolitical and economic challenges; international tourism; medical tourism; dental services; dental tourism; competition; price factors; medical ethics; infrastructure; innovative technologies.